2021
DOI: 10.3389/fmicb.2021.688554
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Fiber Influences Bacterial Community Assembly Processes in the Gut Microbiota of Durco × Bamei Crossbred Pig

Abstract: Several studies have shown that dietary fiber can significantly alter the composition and structure of the gut bacterial community in humans and mammals. However, few researches have been conducted on the dynamics of the bacterial community assembly across different graded levels of dietary fiber in different gut regions. To address this, 24 Durco × Bamei crossbred pigs were randomly assigned to four experimental chows comprising graded levels of dietary fiber. Results showed that the α-and β-diversity of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 77 publications
3
17
0
Order By: Relevance
“…The dramatic changes in the gut microbial communities and the function of such changes in piglets early in life were observed in our study, and the results were in agreement with those of a previous study ( Frese et al, 2015 ; Wang et al, 2019 ; Jurburg and Bossers, 2021 ; Tang et al, 2021 ). With the growth of piglets, the gut microbiota increased in complexity, which is reflected in the increase in microbial richness and evenness.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The dramatic changes in the gut microbial communities and the function of such changes in piglets early in life were observed in our study, and the results were in agreement with those of a previous study ( Frese et al, 2015 ; Wang et al, 2019 ; Jurburg and Bossers, 2021 ; Tang et al, 2021 ). With the growth of piglets, the gut microbiota increased in complexity, which is reflected in the increase in microbial richness and evenness.…”
Section: Discussionsupporting
confidence: 93%
“…However, the potential factors affecting the gut microbiota maturity of newborn piglets still require further study. The capacity for carbohydrate digestion was enhanced, which is consistent with previous studies ( Chu et al, 2017 ; Tang et al, 2021 ; Wu et al, 2021 ). Furthermore, the predicted significant increase in the relative abundances of KEGG pathways associated with amino acid metabolism, especially lysine biosynthesis, further support the enhanced capacity of protein digestion and absorption as the piglets aged.…”
Section: Discussionsupporting
confidence: 92%
“…We predict that white-headed black langurs will have an increased abundance of microbiota taxa associated with cellulose digesting ability in the dry season and will colonize more taxa associated with carbohydrate digestion in the rainy season. (3) High habitat fragmentation limits the food resources of whiteheaded black langurs and could increase the importance of environmental factors in community assembly (Burns et al, 2016;Ning et al, 2019;Tang et al, 2021;. We predict that the value of R 2 based on NCM will be less than 0.5, indicating that the gut microbiota assembly of the langurs will be dominated by deterministic processes.…”
Section: Introductionmentioning
confidence: 94%
“…Furthermore, leaves have lower nutrients and more secondary metabolites than sugar-rich fruits (Que et al, 2022). Previous studies have demonstrated that reduced nutritional levels intensify competition among bacterial taxa, leading to an intensification of deterministic processes (Ning et al, 2019;Tang et al, 2021). For instance, the gut microbial assembly in the jejunum of Duroc × Bamei pigs shifted to deterministic process dominance due to the addition of dietary fiber in the diet (Tang et al, 2021).…”
Section: Seasonal Differences In Community Assemblymentioning
confidence: 99%
“…The abundance of Bacteroidetes and Turicibacter increased with high dietary fiber in cecum and jejunum respectively resulting in alteration of concentration of their metabolites such as bile acids, fatty acids, carbohydrates and carbohydrate conjugate, and organic acids which may potentially influence nutrition absorption [ 107 ]. Tang et al [ 108 ] suggested that adding fibers (Broad bean straw silage) to the basal diet significantly increased the α-diversity of the bacterial community in the jejunum and cecum, while the β-diversity decreased of Durco × Bamei crossbred pigs. Consequently, among the most abundant bacterial genera in the cecum, the relative abundance of unidentified Prevotellaceae and Oscillibacter increased with the increase in dietary fiber, while the richness of Romboutsia, Intestinibacter , and Faecalibacterium , decreased with the increase in dietary fiber.…”
Section: Impact Of Nutritional Intervention On Gut Microbiomementioning
confidence: 99%